Taming XeO3 with aza-crowns: computational studies into σ-hole mediated host-guest interactions - Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2024)
Various aza-crowns with different sizes and substituents have been explored computationally as potential hosts for stabilizing the explosive guest xenon trioxide (XeO3) through sigma-hole-mediated aerogen bonding interactions. Interestingly, aza-crowns demonstrate superior binding towards XeO3 compared to their oxygen and thio counterparts. However, unlike the latter cases, where the binding was found to be increasingly favorable with the increase in the size of the crowns, aza-crowns exhibit a variable size preference for XeO3, peaking with aza-15-crown-5, and reducing thereafter with increase in crown size.
Keywords: aza-crowns; host-guest systems; noncovalent interactions; sigma (sigma) hole; Xenon